Photosynthesis as a temperature indicator in Quercus ilex L. (Global and Planetary Change, 2000)
Net photosynthesis Pn , stomatal conductance gs , leaf temperature LT , transpiration rate . . . . E and in vivo chlorophyll fluorescence were monitored February 1996–February 1997 in Quercus ilex plants growing in the climax area Rome and . in the Garda lake region. Photosynthetic activity is an appropriate temperature-dependent functional trait linked to plant metabolism and performance. We employed photosynthesis as a stress temperature indicator. Regression analysis showed that in such regional climatic conditions, net photosynthetic rates were primarily correlated with temperature. The introduction of rainfall in the function did not significantly improve the theoretical prevision, in the range of temperature and rainfall analysed. The favourable leaf temperatures allowing 90–100% of the highest photosynthetic rates were 14–288C, decreasing over 50% when leaf temperature were respectively below 68C and over 378C: the low potential photochemical efficiency of 0.71 PSII Fv . rFm at Castelporziano during summer, confirmed the state of stress. Transpiration rates remained high with the increase of leaf temperature in summer, in spite of the 46% decrease of stomatal conductance. Nevertheless, this decrease allowed the maintenance of acceptable Pn rates in stressful conditions. The potential productivity of Q. ilex lied on high peaks of activity during periods of lower evaporative demand and a rapid stomatal response to an increase in air temperature and soil water deficit. Although it is difficult to forecast Q. ilex productivity and plant structure, we may hypothesize its future presence in the Mediterranean Basin by the capability of vegetative activity in a wide range of temperatures, the high stomatal control in stressful conditions, the high plasticity index and water use efficiency WUE .